2019
DOI: 10.1136/bmjspcare-2019-001782
|View full text |Cite
|
Sign up to set email alerts
|

End-of-life care in cancer and dementia: a nationwide population-based study of palliative care policy changes

Abstract: ObjectivesThe National Health Insurance programme started providing coverage for inpatient care in palliative care (PC) units of acute care hospitals in 2000; however, initially, only PC provided to patients with terminal cancer was covered. A PC policy that enabled PC reimbursement for patients with dementia was implemented in 2009. However, the association of this PC policy with end-of-life care remains unclear. The study aims to compare the association of the PC policy with end-of-life care between patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…After the passing of the Hospice Palliative Care Act, Taiwan experienced an increase in supportive care use in different intensive care units for stroke patients and a decline in the use of intensive procedures [29]. In addition, population-based studies have found that the implementation of palliative care policies in Taiwan was associated with improved palliative care utilization in connection with cancer, dementia, chronic obstructive pulmonary disease, and stroke [29][30][31].…”
Section: Discussionmentioning
confidence: 99%
“…After the passing of the Hospice Palliative Care Act, Taiwan experienced an increase in supportive care use in different intensive care units for stroke patients and a decline in the use of intensive procedures [29]. In addition, population-based studies have found that the implementation of palliative care policies in Taiwan was associated with improved palliative care utilization in connection with cancer, dementia, chronic obstructive pulmonary disease, and stroke [29][30][31].…”
Section: Discussionmentioning
confidence: 99%
“…Dementia is recognised as a terminal illness. As such, a palliative care approach has been endorsed over the past three decades (Kuo, Lee, Cheung, Chen, & Lin, 2019; Luchins & Hanrahan, 1993; Rango, 1985). The World Health Organization (WHO)’s definition of palliative care describes an “approach that improves the quality of life of patients and their families facing the problem associated with life‐threatening illness, through the prevention and relief of suffering by means of early identification and impeccable assessment and treatment of pain and other problems, physical, psychosocial and spiritual” (World Health, 2014).…”
Section: Introductionmentioning
confidence: 99%